2013
DOI: 10.1186/1471-2172-14-20
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of IL-17 on neural stem cell proliferation and neural cell differentiation

Abstract: BackgroundIL-17, a Th17 cell-derived proinflammatory molecule, has been found to play an important role in the pathogenesis of autoimmune diseases, including multiple sclerosis (MS) and its animal model, experimental autoimmune encephalomyelitis (EAE). While IL-17 receptor (IL-17R) is expressed in many immune-related cells, microglia, and astrocytes, it is not known whether IL-17 exerts a direct effect on neural stem cells (NSCs) and oligodendrocytes, thus inducing inflammatory demyelination in the central ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 45 publications
2
54
0
Order By: Relevance
“…Pro-inflammatory cytokines (e.g., interleukin-17 and interferon g [IFN-g]) released by splenocytes of EAE mice ( Figure S3A) are reported to have an inhibitory effect on NSC proliferation and neural cell differentiation. 34 Our results here showed that NSC differentiation to OLGs was significantly suppressed in the presence of culture supernatants from PLP-specific splenocytes, as shown by decreased cell survival ( Figure S3B), reduced OLG number (CNPase + cells) (Figure S3C), and less OLG arborization (Figures S3D and S3E) compared with PBS-treated controls. However, this impairment of NSC differentiation was overcome by FTY720 (1 nM) ( Figure S3), demonstrating the protective effect of FTY720 during NSC differentiation into OLGs under pathological conditions and possibly during remyelination of already-damaged CNS tissues in MS.…”
Section: Effect Of Fty720 In Nsc Differentiation Into Olgs Under Pathmentioning
confidence: 53%
“…Pro-inflammatory cytokines (e.g., interleukin-17 and interferon g [IFN-g]) released by splenocytes of EAE mice ( Figure S3A) are reported to have an inhibitory effect on NSC proliferation and neural cell differentiation. 34 Our results here showed that NSC differentiation to OLGs was significantly suppressed in the presence of culture supernatants from PLP-specific splenocytes, as shown by decreased cell survival ( Figure S3B), reduced OLG number (CNPase + cells) (Figure S3C), and less OLG arborization (Figures S3D and S3E) compared with PBS-treated controls. However, this impairment of NSC differentiation was overcome by FTY720 (1 nM) ( Figure S3), demonstrating the protective effect of FTY720 during NSC differentiation into OLGs under pathological conditions and possibly during remyelination of already-damaged CNS tissues in MS.…”
Section: Effect Of Fty720 In Nsc Differentiation Into Olgs Under Pathmentioning
confidence: 53%
“…Previous observations are mechanistically supported by in vitro findings, which demonstrate Th17-induced neuronal injury mediated by deleterious elevations of intracellular Ca 2+ levels in neurons. Indeed, basal expression of the IL-17RA has been shown for various neuronal populations [10,54], and it can be potently up-regulated in pathological conditions such as, for example, focal cortical dysplasia [29]. One particularly sensitive target for IL-17A-mediated neuronal damage is the neural stem cells (NSCs) of the subventricular and subgranular zone of the hippocampus.…”
Section: Il-17 In Ms and Eaementioning
confidence: 99%
“…The addition of IL-17 to NSC cultures does not induce apoptosis in these cells but markedly suppresses neurosphere growth in vitro. Moreover, IL-17A inhibits NSC proliferation in a p38 MAPK-dependent manner and constrains NSC differentiation, especially into astrocytic and NG2 lineages [54]. However, IL-17A can also have neurotrophic properties.…”
Section: Il-17 In Ms and Eaementioning
confidence: 99%
“…Taken together, astrocyte-intrinsic IL-17A mediated signaling seems to promote CNS inflammation. However, recent conflicting data concerning the effects of IL-17A on neuronal stem cells and oligodendrocyte precursor cells(25) highlight the need for further investigations before targeting this immune axis in cell-type specific therapies for Multiple Sclerosis.…”
Section: Role Of Selected Pro- and Anti-inflammatory Cytokinesmentioning
confidence: 99%